Recent advances in analysis of capsaicin and its effects on metabolic pathways by mass spectrometry - Peng, Zifang; Zhang, Wenfen; Zhang, Xu; Mao, Jian; Zhang, Qidong; Zhao, Wuduo; Zhang, Shusheng; Xie, Jianping (Frontiers in Nutrition, 2023)
Capsaicin is the main food active component in Capsicum that has gained considerable attention due to its broad biological activities, including antioxidation, antiinflammation, anti-tumor, weight regulation, cardiac protection, anti-calculi, and diurnal-circadian regulation. The potent biological effects of capsaicin are intimately related to metabolic pathways such as lipid metabolism, energy metabolism, and antioxidant stress. Mass spectrometry (MS) has emerged as an effective tool for deciphering the mechanisms underlying capsaicin metabolism and its biological impacts. However, it remains challenging to accurately identify and quantify capsaicin and its self-metabolites in complex food and biological samples, and to integrate multiomics data generated from MS. In this work, we summarized recent advances in the detection of capsaicin and its self-metabolites using MS and discussed the relevant MSbased studies of metabolic pathways. Furthermore, we discussed current issues and future directions in this field. In-depth studies of capsaicin metabolism and its physiological functions based on MS is anticipated to yield new insights and methods for preventing and treating a wide range of diseases.